2019
DOI: 10.4271/2019-01-0049
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of FAME and Diesel Fuel Composition on Stability and Vehicle Filter Blocking

Abstract: In recent years, there has been an impetus in the automotive industry to develop newer diesel injection systems with a view to reducing fuel consumption and emissions. This development has led to hardware capable of higher pressures, typically up to 2500 bar. An increase in pressure will result in a corresponding increase in fuel temperature after compression with studies showing changes in fuel temperatures of up to 150 °C in 1000-2500 bar injection systems.Until recently, the addition of Fatty Acid Methyl Es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…It was found that the presence of biodiesel had no effect on the clogging characteristics compared to conventional diesel, and the presence of aromatics and derivatives of nitrogen has a much more detrimental effect on oxidative stability. This is in accordance with a recent study, which focused on identifying the factors responsible for filter clogging by using a filter rig on a High-Pressure Common Rail (HPCR) system (Gopalan et al 2019). Furthermore, filter blockage can occur due to the accumulation of other impurities within the diesel engine filtration system.…”
Section: Introductionsupporting
confidence: 89%
“…It was found that the presence of biodiesel had no effect on the clogging characteristics compared to conventional diesel, and the presence of aromatics and derivatives of nitrogen has a much more detrimental effect on oxidative stability. This is in accordance with a recent study, which focused on identifying the factors responsible for filter clogging by using a filter rig on a High-Pressure Common Rail (HPCR) system (Gopalan et al 2019). Furthermore, filter blockage can occur due to the accumulation of other impurities within the diesel engine filtration system.…”
Section: Introductionsupporting
confidence: 89%
“…Injector deposits have been found in a number of locations in the injector, on the nozzle tip and in the spray holes external injector deposits (EDID) and since around 2008 internally on the push rod, the upper and lower springs and the needle. Though investigated for some time, these internal injector deposits (IDID) continue to be studied by groups worldwide because of their importance to the industry and a need to understand fully their nature [25][26][27][28][29][30][31][32][33]. Initial analysis by a number of groups contributed to identifying the deposits formed, leading to their classification in six distinct groups:…”
Section: Excerpts From History: Analytical Testingmentioning
confidence: 99%
“…The use of high-percentage biodiesel blends is known to be associated with fuel injector deposits [11] and other types of injection system effects [12,13]. On the other hand, US and European market fuel surveys indicate that many retail biodiesel samples are out of specification, which means that poor quality biodiesel is not scarce [14,15].…”
Section: Biodiesel Fuel Quality and Stability Problemsmentioning
confidence: 99%
“…The most demanding issue with the use of biodiesel is its oxidation stability, which affects performance, emissions, and engine durability ( Figure 1). The more general term biodiesel degradation is referred to the modification of its original composition and properties due to aging, oxidation, and metal corrosion during the storage process [12,16]. The compatibility of seal and hose materials commonly encountered in automotive fuel systems using conventional hydrocarbon fuels has long been established and elastomer manufacturers are able to make recommendations for their use.…”
Section: Biodiesel Fuel Quality and Stability Problemsmentioning
confidence: 99%